Bibliometric Analysis of Oral Presentations with Mobile Technology in Tertiary Education - Rachman, Dzul; Khusnul Khatimah; I Putu Indra Kusuma; Marianus Roni (Script Journal: Journal of Linguistics and English Teaching, 2024)
Background: Oral presentations, vital for assessing student understanding and communication skills in higher education, are enhanced by peer feedback and video recording. However, language anxieties necessitate supportive strategies. This study explores mobile technology's role in presentations via a bibliometric analysis.Methodology: This study uses bibliometric analysis to track research trends in mobile technology use in higher education oral presentations from 2014 to 2023. Data was gathered from the Dimensions database and analyzed with Excel and VOSviewer, revealing publication and citation trends, top researchers, thematic clusters, and research categories.Findings: Research output rose steadily until 2017, then surged in 2020 due to the Covid-19 pandemic. Rising citations reflect enduring impact. The focus is on education, with contributions from various disciplines. Global collaboration is evident among top researchers.Conclusion: The study finds that mobile tech-based oral presentations are crucial in higher education, promoting learning and skills. It underscores research resilience and adaptability to global challenges like the Covid-19 pandemic, providing valuable insights for future research and teaching practices.Originality: This study explores trends in oral presentations with mobile technology in higher education via a detailed bibliometric analysis. It provides insights into research output, citation impact, and thematic clusters, contributing to the dialogue on effective teaching and assessment practices.